Судовий захист прав неповнолітніх - Лаленков, С. М.; Lalenkov, S. M. (Право і суспільство. - 2023. - №3. - С. 111-116, 2023)
Стаття присвячена аналізу судового захисту прав неповнолітніх і його ролі у забезпеченні справедливості та захисті їхніх прав. Розглянуто сутність та характеристики судового захисту прав неповнолітніх з урахуванням міжнародних стандартів та національного законодавства. Проведено аналіз процесу судового захисту прав неповнолітніх. Висвітлено важливі аспекти, такі як представництво інтересів неповнолітнього, принципи справедливості та специфіка процесуальних гарантій для неповнолітніх у судових процедурах.

This article is devoted to the analysis of judicial protection of the rights of minors and its role in ensuring justice and protecting their rights. The essence and characteristics of judicial protection of the rights of minors are considered, taking into account international standards and national legislation. An analysis of the process of legal protection of the rights of minors, in particular as participants in the legal process, was carried out. Important aspects such as the representation of the minor's interests, the principles of justice and the specifics of procedural guarantees for minors in court procedures are highlighted. The article also considers the main problems that minors face during the judicial protection of their rights. These problems include insufficient accessibility and comprehensibility of legal procedures for minors, insufficient representation of their interests, and failure to ensure confidentiality. In order to improve the judicial protection of the rights of minors, a number of legislative recommendations and measures that can be adopted at the legislative level are proposed. These measures include the implementation of the expansion of the specialization of judges at the legislative level. increasing education of minors regarding their rights and procedures, ensuring proper representation of their interests, as well as strengthening guarantees of confidentiality and protection of personal data. The importance of ensuring effective judicial protection of the rights of minors is emphasized. Ensuring fair and unhindered access to justice for minors is a necessary condition for protecting their rights and interests. It is necessary to carry out systematic measures to improve legal education among minors, ensure adequate representation of their interests in court and ensure confidentiality and protection of personal data. Achieving fair judicial protection of the rights of minors is an important component of building a just and humane society. The need for further research and development of effective strategies and policies aimed at strengthening the judicial protection of the rights of minors, taking into account their unique needs and characteristics, is emphasized.

Статья посвящена анализу судебной защиты прав несовершеннолетних и его роли в обеспечении справедливости и защите их прав. Рассмотрена сущность и характеристики судебной защиты прав несовершеннолетних с учетом международных стандартов и национального законодательства. Проведен анализ процесса судебной защиты прав несовершеннолетних. Освещены важные аспекты, такие как представительство интересов несовершеннолетнего, принципы справедливости и специфика процессуальных гарантий для несовершеннолетних в судебных процедурах.
Judicial protection of the rights of minors
Keywords: неповнолітні; minors; несовершеннолетние; судовий захист; judicial protection; судебная защита; захист прав неповнолінтніх; protection of the rights of minors; защита прав несовершеннолетних; права та інтереси; rights and interests; права и интересы; правові процедури; legal procedures; правовые процедуры